Pengaruh Biaya Pendidikan, Promosi dan Citra Universitas terhadap Keputusan Mahasiswa dalam Memilih Program Studi di Seni Murni - Lea Sepvianty Suharso; Surya Setyawan (Publikasi Indonesia, 2025)
Education costs, promotion and university image are one of the factors that can influence students' decisions in choosing a study program. This research aims to find out whether there is an influence of education costs, promotions and university image on students' decisions to choose the Fine Arts Study Program. Using quantitative methods, data was collected from 30 active student respondents in the Fine Arts Undergraduate Program. The results of the analysis show that the cost of education and the image of the university have a significant positive influence on student decisions. Meanwhile, promotion did not show a significant influence on this decision. This conclusion shows the importance of universities considering educational costs and building a good image in attracting prospective students. It is hoped that this research can provide knowledge to universities in formulating effective marketing strategies.